Assimilation, Resilience, and Survival : A History of the Stewart Indian School, 1890-2020 - Williams, Samantha M. (Book collections on Project MUSE., 2022)
"Assimilation, Resilience, and Survival is the first book to explore the trauma of the boarding school experience at Steward Indian School and the resilience of generations of students who persevered there under the most challenging of circumstances"--